Navigating uncertainties: collaborative approaches to science-policy dialogues - Marie Heidenreich; Marie Heidenreich; Almut Brunner; Andrea Meyn; Katharina Sielemann; Katharina Sielemann (Frontiers in Earth Science)
Science-policy dialogues are becoming increasingly relevant for guiding evidence-based action on complex environmental challenges, such as marine conservation. Yet, effective communication of scientific insights to policymakers remains difficult due to persistent uncertainties, complex problems, and the need for timely, actionable knowledge. This perspective paper explores the organization of effective science-policy dialogues, focusing on key challenges such as communicating uncertainty and establishing shared core messages. To address these challenges, we propose a structured approach that includes: (1) identifying specific policy information needs, (2) coordinating interdisciplinary, multi-institutional research teams, (3) tailoring scientific findings into clear, audience-focused core messages and options for actions, (4) conducting targeted dialogue events with policymakers, and (5) evaluating the dialogue process for continuous improvement. Drawing on experiences at the science-policy interface and case studies from German research institutions on sea-level rise and carbon dioxide removal, we present strategies for developing evidence-based core messages that resonate with policymakers. Our approach highlights the value of collaborative efforts among multiple research institutions, enabling a unified scientific voice that establishes both credibility and acceptance among policymakers. This upstream coordination process between different disciplines and institutions also improves the scientific quality of policy advice. Ultimately, this article advocates a structured, collaborative approach to science-policy dialogues, reinforcing the critical role of science in shaping robust, evidence-based environmental policy.